Light ready-mixed mortar for green building and preparation method of light ready-mixed mortar
By using clay sintered ceram and chitosan/corn core particle composites in lightweight premixed mortar for green buildings, the problems of insufficient insulation and anti-dry shrinkage performance of existing mortars are solved, and efficient insulation and stable volume performance are achieved.
Patent Information
- Application Number
- CN202411792435.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-07
- Publication Date
- 2025-03-14
AI Technical Summary
The existing lightweight premixed mortar for green buildings has problems such as poor insulation and thermal insulation performance and poor dry shrinkage resistance.
The lightweight premixed mortar for green building was prepared by selecting clay sintered ceram as coarse aggregate and combining chitosan/corn core particle composite as insulation particles.
It has achieved lightweight, high-strength, good volume stability and excellent thermal performance in green buildings. It has significant insulation effect, safe and environmentally friendly use, and is suitable for a variety of construction projects.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a lightweight premixed mortar for green building and a preparation method thereof. Background Art
[0002] Building energy conservation urgently needs safe, environmentally friendly and efficient insulation materials. Insulation mortar is a powder insulation material obtained by mixing lightweight aggregate, cementitious materials and chemical additives. Compared with various insulation boards, it has the advantages of convenient construction, good integrity with the wall, good safety and durability.
[0003] At present, there are many types of thermal insulation mortars used in wall construction, and their performance varies. The most common ones are: EPS particle thermal insulation mortar, expanded perlite thermal insulation mortar, and vitrified microsphere thermal insulation mortar. Among them, although EPS particle thermal insulation mortar has the advantages of good thermal insulation performance and good corrosion resistance, EPS is an organic lightweight material, which causes poor workability of the mortar, great construction difficulty, low bonding force, and poor fire resistance. In particular, organic materials will release harmful substances, so it is not suitable for large-scale promotion and use; due to the open-pore structure of expanded perlite thermal insulation mortar, its gaps are filled with cement during the mortar mixing process, which greatly reduces its thermal insulation performance; in addition, this type of mortar has a large water absorption rate and poor freeze-thaw resistance. The mortar is prone to water loss and shrinkage cracks during the coagulation and hardening process; the thermal insulation mortar with vitrified microspheres has good thermal insulation performance, but due to the small particle size and poor strength of the vitrified microspheres, the strength of the mortar is low, which makes it difficult to apply to engineering projects with high masonry strength requirements. Therefore, there is an urgent need to develop a lightweight premix for green building that has significant thermal insulation effect, is safe and environmentally friendly to use, has excellent mechanical properties, and has low production cost. Summary of the invention
[0004] The purpose of the present invention is to provide a lightweight premixed mortar for green building and a preparation method thereof, so as to solve the following technical problems:
[0005] The existing lightweight premixed mortar for green buildings has the problems of poor thermal insulation performance and poor anti-shrinkage performance.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A lightweight premixed mortar for green building, comprising at least the following components:
[0008] 35-40 parts of cement, 10-30 parts of fly ash, 0-10 parts of fine aggregate, 15-20 parts of sintered clay pellets, 5-10 parts of vitrified microspheres, 2-10 parts of corncob particles, 1-4 parts of hybrid chitosan, and 0.1-3 parts of water reducer.
[0009] As a further embodiment of the present invention: the fine aggregate comprises at least one of natural river sand, machine-made sand or pottery sand, and the bulk density of the fine aggregate is 730-800 kg / m 3 , particle size is 0.5-5.5mm.
[0010] As a further embodiment of the present invention: the bulk density of the corncob particles is 120-220 kg / m 3 , particle size is 0.1-2.5mm, and at least includes corn cob particles with a particle size of 2.5-5.0mm, 1.25-2.5mm, 0.16-1.25mm or 0-0.16mm.
[0011] As a further embodiment of the present invention: the bulk density of the clay sintered ceramsite is 220-500 kg / m 3 , the particle size is 5-10mm, and the water reducer is at least one of naphthalenesulfonate water reducer, melamine water reducer, lignin sulfonate or polycarboxylic acid high-efficiency water reducer.
[0012] As a further solution of the present invention: the closed porosity of the vitrified microspheres is 88-98%, and the bulk density is 85-100 g / m 3 , and at least includes vitrified microbeads with a particle size of 10-40 mesh or a particle size of 60-100 mesh.
[0013] A method for preparing lightweight premixed mortar for green building, comprising at least the following steps:
[0014] Weigh each raw material according to the formula;
[0015] Chitosan / corncob particle composites were obtained by vacuum impregnation of corncob particles with hybrid chitosan, followed by solvent exchange, aging, and drying;
[0016] Cement, fly ash, fine aggregate, water reducing agent, clay sintered ceramsite, chitosan / corn cob particle composite, vitrified microspheres and water are stirred and mixed to obtain a lightweight premixed mortar for green building.
[0017] As a further solution of the present invention: the rotation speed of the stirring and mixing is 50-100 r / min and the time is 10-30 min.
[0018] As a further embodiment of the present invention: the preparation method of the hybrid chitosan comprises the following steps:
[0019] Dropping nanocellulose into the polyvinyl alcohol solution and stirring to form a uniform liquid mixture;
[0020] pouring the liquid mixture into the acidified chitosan solution and stirring to obtain a mixed solution;
[0021] The cross-linking agent is dropped into the mixed solution and the mixture is stirred continuously to obtain a hybrid chitosan sol.
[0022] As a further solution of the present invention: the mass ratio of the nanocellulose, the polyvinyl alcohol and the chitosan is 1:3-5:6-8, the aspect ratio of the nanocellulose is 30-40, and the cross-linking agent is dicumyl peroxide.
[0023] Beneficial effects of the present invention:
[0024] The present invention selects clay sintered ceramsite as coarse aggregate and chitosan / corn cob particle composite as thermal insulation particles. The interaction between the raw materials makes the prepared green building lightweight premixed mortar light and high-strength, good volume stability, excellent thermal performance, and significant thermal insulation effect. It is safe and environmentally friendly to use and can be widely used in the floor of heated kangs in apartments and houses, roof insulation concrete, the bottom of parking lots and the bottom of basements in construction work. Specifically, the present invention selects clay sintered ceramsite as coarse aggregate. Compared with coarse aggregates such as crushed gravel, clay sintered ceramsite is lighter, effectively reducing the deadweight of the building and the burden on the foundation load. It has excellent resistance to shrinkage deformation and damage, and has good workability and thermal insulation. The grading optimization of clay sintered ceramsite also plays an important role in improving the strength of mortar and reducing the shrinkage rate of mortar.
[0025] The present invention also uses hybrid chitosan and corncob particles for compounding, and uses corncob particles as a matrix to construct a network framework, thereby enhancing the network skeleton structure from a macroscopic perspective, and while ensuring thermal insulation performance, greatly reducing the problem of large-scale shrinkage of hybrid chitosan aerogel. During the gelation, aging and solvent exchange process, the microporous skeleton network framework provided by the corncob particles can successfully inhibit substantial shrinkage. At the same time, during the drying process, this framework can not only effectively reduce the capillary force generated during the drying process, but also provide strong support for the formation of the three-dimensional network structure of the hybrid chitosan aerogel. Chitosan is hybridized with nanocellulose and polyvinyl alcohol. The introduction of nanocellulose with a suitable aspect ratio can effectively regulate and improve the micro-nanoscale network structure layer in an interlaced manner, and the network skeleton structure of the hybrid chitosan aerogel is enhanced by irregular physical entanglement, effectively inhibiting the shrinkage of the chitosan aerogel before and after drying, and the crosslinking effect between the crosslinker and the linear polymer polyvinyl alcohol can further control the shrinkage. There are also a large number of -OH, polar groups -OH and -OH / -NH on the surface of polyvinyl alcohol. 2Hydrogen bonds are generated between them, similar to the role of a cross-linking agent, promoting the polymerization between nanocellulose and chitosan. In addition, the vitrified microspheres in the mortar component can play a role in heat preservation, sound absorption, fire prevention, reducing bulk density and improving grading. Fly ash can improve the workability of the mortar, reduce the amount of cement, and reduce the cost of the mortar. After adding, it can not only synergize with other raw materials to play a reinforcing role, but also have an anti-cracking effect. The corn cob particles and clay sintered ceramsite added to the lightweight premixed mortar for green buildings are all waste recycling and reuse, realizing the transformation of waste into treasure, which not only saves resources but also is beneficial to environmental protection. DETAILED DESCRIPTION
[0026] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1
[0028] The preparation method of hybrid chitosan comprises the following steps:
[0029] 20 g of nanocellulose (2.5 wt.%) was slowly dropped into 90 g of polyvinyl alcohol (4 wt.%) solution and stirred for 30 min to form a uniform liquid mixture;
[0030] The mixture was slowly poured into 150 g (10 g / L) chitosan solution, wherein the acidified chitosan solution was composed of 2 wt.% acetic acid solvent (40 vol.%, ≥99.5%) and ethanol (60 vol.%), and the mixture was stirred continuously for 0.5 h at 10° C. to obtain a mixed solution;
[0031] At an ambient temperature of 10° C., 60 g of cross-linking agent dicumyl peroxide (8 wt.%) was slowly dripped into the mixed solution and stirred for 10 min to form a hybrid chitosan sol.
[0032] The preparation method of lightweight premixed mortar for green building comprises the following steps:
[0033] Weigh 40kg cement, 10kg fly ash, 5kg ceramic sand, 10kg vitrified microspheres, 20kg clay sintered ceramsite, 4kg corncob particles, 0.1kg polycarboxylic acid high-efficiency water reducer, 2kg hybrid chitosan, and 40kg water;
[0034] The mixture was washed with ethanol for 12 hours, and then placed in a drying oven for drying. After natural cooling, the mixture was placed in a low temperature environment of 10°C for 12 hours. The hybrid chitosan sol and corn cob particles obtained above were placed in a vacuum impregnation tank. After vacuum impregnation for 1 hour, the mixture was placed in the vacuum impregnation tank for 1-2 hours and then taken out for solvent exchange, aging and drying to obtain a chitosan / corn cob particle composite.
[0035] Cement, fly ash, ceramic sand, vitrified microspheres, clay sintered ceramsite, chitosan / corn cob particle composite, polycarboxylic acid high-efficiency water reducing agent and water were mixed and stirred at a speed of 60 r / min for 15 minutes to obtain a lightweight premixed mortar for green building.
[0036] Example 2
[0037] The preparation method of hybrid chitosan comprises the following steps:
[0038] 30 g of nanocellulose (2.5 wt.%) was slowly dropped into 90 g of polyvinyl alcohol (4 wt.%) solution and stirred for 30 min to form a uniform liquid mixture;
[0039] The mixture was slowly poured into 150 g (10 g / L) chitosan solution, wherein the acidified chitosan solution was composed of 2 wt.% acetic acid solvent (40 vol.%, ≥99.5%) and ethanol (60 vol.%), and the mixture was stirred continuously for 0.5 h at 10° C. to obtain a mixed solution;
[0040] At an ambient temperature of 10° C., 60 g of a crosslinking agent, dicumyl peroxide (8 wt.%), was slowly dripped into the mixed solution and stirred for 10 min to form a hybrid chitosan sol;
[0041] The remaining components and preparation method are exactly the same as those in Example 1.
[0042] Example 3
[0043] The preparation method of hybrid chitosan comprises the following steps:
[0044] 20 g of nanocellulose (2.5 wt.%) was slowly dropped into 100 g of polyvinyl alcohol (4 wt.%) solution and stirred for 30 min to form a uniform liquid mixture;
[0045] The mixture was slowly poured into 150 g (10 g / L) chitosan solution, wherein the acidified chitosan solution was composed of 2 wt.% acetic acid solvent (40 vol.%, ≥99.5%) and ethanol (60 vol.%), and the mixture was stirred continuously for 0.5 h at 10° C. to obtain a mixed solution;
[0046] At an ambient temperature of 10° C., 60 g of a crosslinking agent, dicumyl peroxide (8 wt.%), was slowly dripped into the mixed solution and stirred for 10 min to form a hybrid chitosan sol;
[0047] The remaining components and preparation method are exactly the same as those in Example 1.
[0048] Example 4
[0049] The preparation method of lightweight premixed mortar for green building comprises the following steps:
[0050] Weigh 40kg cement, 20kg fly ash, 5kg ceramic sand, 10kg vitrified microspheres, 20kg clay sintered ceramsite, 5kg corncob particles, 0.1kg polycarboxylic acid high-efficiency water reducing agent, 2kg hybrid chitosan, and 40kg water;
[0051] The remaining components and preparation method are exactly the same as those in Example 1.
[0052] Example 5
[0053] The preparation method of lightweight premixed mortar for green building comprises the following steps:
[0054] Weigh 40kg cement, 10kg fly ash, 5kg ceramic sand, 10kg vitrified microspheres, 20kg clay sintered ceramsite, 4kg corncob particles, 0.1kg polycarboxylic acid high-efficiency water reducer, 4kg hybrid chitosan, and 40kg water;
[0055] The remaining components and preparation method are exactly the same as those in Example 1.
[0056] Comparative Example 1
[0057] The preparation method of chitosan hybrid aerogel comprises the following steps:
[0058] 20 g of nanocellulose (2.5 wt.%) was slowly dropped into 90 g of polyvinyl alcohol (4 wt.%) solution and stirred for 30 min to form a uniform liquid mixture;
[0059] The mixture was slowly poured into 150 g (10 g / L) chitosan solution, wherein the acidified chitosan solution was composed of 2 wt.% acetic acid solvent (40 vol.%, ≥99.5%) and ethanol (60 vol.%), and the mixture was stirred continuously for 0.5 h at 10° C. to obtain a mixed solution;
[0060] At an ambient temperature of 10° C., 60 g of a crosslinking agent, dicumyl peroxide (8 wt.%), was slowly dripped into the mixed solution and stirred for 10 min to form a hybrid chitosan sol;
[0061] The hybrid chitosan sol was poured into a mold and allowed to stand at a low temperature of 20°C for 12 h. Solvent exchange and gel aging were carried out in a constant temperature water bath with a temperature increase gradient of 10°C every 48 h and once every 24 h until the temperature reached 75°C. The hybrid chitosan aerogel was obtained by drying at supercritical conditions of 60°C and 18 MPa for 12 h.
[0062] The preparation method of lightweight premixed mortar for green building comprises the following steps:
[0063] Weigh 40 kg of cement, 10 kg of fly ash, 5 kg of ceramic sand, 10 kg of vitrified microspheres, 20 kg of clay sintered ceramsite, 4 kg of corn cob particles, 0.1 kg of polycarboxylic acid high-efficiency water reducer, 2 kg of chitosan hybrid aerogel and 40 kg of water, mix and stir at a speed of 60 r / min for 15 min to obtain mortar.
[0064] Comparative Example 2
[0065] The preparation steps of hybrid chitosan were omitted, and 40 kg of cement, 10 kg of fly ash, 5 kg of pottery sand, 10 kg of vitrified microspheres, 20 kg of clay sintered ceramsite, 4 kg of corncob particles, 0.1 kg of polycarboxylic acid high-efficiency water reducing agent and 40 kg of water were weighed and mixed and stirred at a speed of 60 r / min for 15 min to obtain mortar.
[0066] Comparative Example 3
[0067] Weigh 20 kg of crushed gravel, directly mix and stir cement, fly ash, ceramic sand, vitrified microspheres, crushed gravel, chitosan / corn cob particle composite, polycarboxylic acid high-efficiency water reducer and water at a speed of 60 r / min for 15 min to obtain mortar;
[0068] The remaining components and preparation method are exactly the same as those in Example 1.
[0069] Comparative Example 4
[0070] The step of preparing the chitosan / corncob particle composite is omitted, and cement, fly ash, ceramic sand, vitrified microspheres, clay sintered ceramsite, chitosan hybrid aerogel, corncob particles, polycarboxylic acid high-efficiency water reducing agent and water are directly mixed and stirred at a speed of 60 r / min for 15 minutes to obtain mortar;
[0071] The remaining components and preparation method are exactly the same as those in Comparative Example 1.
[0072] Performance Testing
[0073] The lightweight premixed mortar for green building obtained in Examples 1-5 and Comparative Examples 1-4 was transferred into a test mold, and a test piece with a size of 300 mm×300 mm×30 mm was formed and cured, and dried in a constant temperature oven until the weight no longer changed. The density and compressive strength were measured according to JGJ70-90 "Test Method for Basic Properties of Building Mortar", the bonding strength was measured according to JGJ110-98 "Test Standard for Bond Strength of Facing Bricks in Building Engineering", the thermal conductivity was measured according to JGJ51-90 "Technical Code for Lightweight Aggregate Concrete", and the shrinkage was measured according to JGJ70-90 "Test Method for Basic Properties of Building Mortar". The test results are shown in Table 1;
[0074] Table 1: Statistical table of performance test data of Examples 1-5 and Comparative Examples 1-4
[0075]
[0076] As shown in Table 1, the lightweight premixed mortar for green building proposed by the present invention has the advantages of high compressive strength, high bonding strength, low thermal conductivity and small shrinkage. All performance indicators meet or exceed relevant standards and actual engineering requirements, and can be used as energy-saving and efficient thermal insulation materials for building walls, and widely promoted and applied in various building energy-saving projects. Compared with Comparative Examples 1, 2 and 4, the thermal conductivity and drying shrinkage of the mortar obtained in Comparative Examples 1, 2 and 4 are relatively high, indicating that only adding chitosan aerogel, only adding corncob particles, or directly adding chitosan aerogel and corncob particles, the improvement of the thermal insulation performance and shrinkage performance of the mortar is poor, and the use of hybrid chitosan composite corncob particles can produce a good synergistic effect, so that the obtained mortar has good thermal insulation performance and shrinkage performance. Compared with Example 3, in Example 3, crushed gravel is used as coarse aggregate, and the compressive strength of the mortar obtained remains unchanged, but the thermal conductivity and drying shrinkage are improved, indicating that selecting clay sintered expanded clay as coarse aggregate can effectively reduce the bulk density of concrete, and the strength of the mortar obtained is not reduced, and the thermal insulation performance and drying shrinkage performance of the mortar can also be improved.
[0077] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A lightweight premixed mortar for green building, characterized in that: At least the following components are included: 35-40 parts of cement, 10-30 parts of fly ash, 0-10 parts of fine aggregate, 15-20 parts of sintered clay pellets, 5-10 parts of vitrified microspheres, 2-10 parts of corncob particles, 1-4 parts of hybrid chitosan, and 0.1-3 parts of water reducer.
2. A lightweight premixed mortar for green building according to claim 1, characterized in that: The fine aggregate comprises at least one of natural river sand, machine-made sand or pottery sand, and the bulk density of the fine aggregate is 730-800 kg / m 3 , particle size is 0.5-5.5mm.
3. A lightweight premixed mortar for green building according to claim 1, characterized in that: The bulk density of the corncob particles is 120-220 kg / m 3 , particle size is 0.1-2.5mm, and at least includes corn cob particles with a particle size of 2.5-5.0mm, 1.25-2.5mm, 0.16-1.25mm or 0-0.16mm.
4. The lightweight premixed mortar for green building according to claim 1, characterized in that: The bulk density of the clay sintered ceramsite is 220-500kg / m 3 , the particle size is 5-10mm, and the water reducer is at least one of naphthalenesulfonate water reducer, melamine water reducer, lignin sulfonate or polycarboxylic acid high-efficiency water reducer.
5. The lightweight premixed mortar for green building according to claim 1, characterized in that: The closed porosity of the vitrified microspheres is 88-98%, and the bulk density is 85-100 g / m 3 , and at least includes vitrified microbeads with a particle size of 10-40 mesh or a particle size of 60-100 mesh.
6. A method for preparing lightweight premixed mortar for green building, characterized in that: At least the following steps are included: Weigh each raw material according to the formula; The chitosan / corncob particle composites were obtained by vacuum impregnation of corncob particles with hybrid chitosan, followed by solvent exchange, aging, and drying; Cement, fly ash, fine aggregate, water reducing agent, clay sintered ceramsite, chitosan / corn cob particle composite, vitrified microspheres and water are stirred and mixed to obtain a lightweight premixed mortar for green building.
7. The method for preparing a lightweight premixed mortar for green building according to claim 6, characterized in that: The stirring and mixing is performed at a rotation speed of 50-100 r / min and a time of 10-30 min.
8. The method for preparing a lightweight premixed mortar for green building according to claim 6, characterized in that: The preparation method of the hybrid chitosan comprises the following steps: Dropping nanocellulose into the polyvinyl alcohol solution and stirring to form a uniform liquid mixture; pouring the liquid mixture into the acidified chitosan solution and stirring to obtain a mixed solution; The cross-linking agent is dropped into the mixed solution and stirring is continued to obtain a hybrid chitosan sol.
9. The method for preparing a lightweight premixed mortar for green building according to claim 8, characterized in that: The mass ratio of the nanocellulose, the polyvinyl alcohol and the chitosan is 1:3-5:6-8, the aspect ratio of the nanocellulose is 30-40, and the cross-linking agent is dicumyl peroxide.